2022
DOI: 10.1111/ffe.13832
|View full text |Cite
|
Sign up to set email alerts
|

Remnant tensile and creep properties of aluminized AISI 321 austenite stainless steel under prior creep–fatigue interaction

Abstract: Aluminized AISI 321 steels applied as heat exchange tube are generally subjected to creep-fatigue (C-F) exposure during service. Remaining tensile and creep performance of this steel at 620 C were therefore studied under prior C-F deformation. Results revealed that residual properties exhibit an initial increase and followed degradation with rising lifetime fraction of prior C-F.The tensile strength and creep lifespan reach highest at 30% lifetime fraction, since dislocation cell networks are well developed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…39 Detailed reasons can refer to our previous work. 33,34 As shown in Figure 6A,C, clear decreases in the creep strain were observed with the prior C-F lifetime increasing from 0 to 50% for the uncoated and self-healing steel at the same creep time. However, with the prior C-F lifetime further increasing to 80%, the creep strain of the sample with same creep time increased sharply but is still lower than that of the undeformed sample with prior C-F lifetime of 0%.…”
Section: Influence Of Self-healing Coating On Remnant Creep Propertie...mentioning
confidence: 79%
See 3 more Smart Citations
“…39 Detailed reasons can refer to our previous work. 33,34 As shown in Figure 6A,C, clear decreases in the creep strain were observed with the prior C-F lifetime increasing from 0 to 50% for the uncoated and self-healing steel at the same creep time. However, with the prior C-F lifetime further increasing to 80%, the creep strain of the sample with same creep time increased sharply but is still lower than that of the undeformed sample with prior C-F lifetime of 0%.…”
Section: Influence Of Self-healing Coating On Remnant Creep Propertie...mentioning
confidence: 79%
“…These results are consistent with the previous studies, [35][36][37] and detailed explanation for such phenomena can refer to our previous studies. 33,34 Clear influence of coating on the C-F behavior of 321 steel can also be observed. In detail, at the same C-F conditions, the lowest cyclic strain is shown in the self-healing 321 steel, while the highest in aluminized 321 steel.…”
Section: Influence Of Self-healing Coating On the C-f Properties Of 3...mentioning
confidence: 91%
See 2 more Smart Citations
“…Some authors focused on the material properties and damage mechanisms. Chen et al 8 employed microstructural characterizations to reveal remaining mechanical and creep performance of aluminized AISI 321 steels at 620°C under prior C‐F deformation. The results showed that with the increase of life fraction of prior C‐F, the residual properties increased first and then decreased.…”
mentioning
confidence: 99%